Implementation of the Kaizen Method in the Qur'an Memorization (Tahfidz) Learning Process at Zhilalul Qur'an Islamic Boarding School in Jepara - Ellisa Nailizzulfa; Sukarman Sukarman; Muhammad Khoiruddin (MASI Mandiri Edukasi, 2026)
Improving the quality of Qur'an memorization (tahfidz) learning poses a significant challenge in Islamic education management, particularly in Islamic boarding schools (pondok pesantren) oriented toward achieving and maintaining high-quality student memorization. Therefore, a learning management system capable of driving continuous improvement is essential to ensure the quality of both the learning process and its outcomes. This study aims to analyze the implementation of the Kaizen method in the tahfidz learning process at Zhilalul Qur'an Islamic Boarding School in Jepara. The research employs a qualitative approach with a field research design. Data were gathered through in-depth interviews, observation, and documentation, involving the boarding school caretakers, the head of the tahfidz program, and tahfidz students as research informants. Data analysis followed the Miles, Huberman, and Saldaña model, which includes data reduction, data display, and conclusion drawing. The results show that Kaizen principles are applied by grouping students by memorization level, setting measurable memorization targets, conducting lessons using a classical-individual method, conducting daily evaluations of students' memorization progress, and providing special assistance to students who fall behind in their memorization targets. Furthermore, a culture of continuous improvement is reinforced through a post-khatam (completion) program that requires students who have finished their memorization to strengthen their retention before receiving certification (syahadah). The findings indicate that implementing Kaizen through a cycle of planning, implementation, evaluation, and follow-up contributes to sustaining and continuously enhancing the quality of tahfidz learning at Zhilalul Qur'an Islamic Boarding School in Jepara.